INSTALASI PENERANGAN JALAN UMUM BERBASIS SOLAR CELL DAN PHOTOCELL DI DESA CILANGKARA KABUPATEN BEKASI - Ramadhan, Dickyansyah; Amin Ash Shabah, Musyaffa; Rahmawati, Rafika (An-Nizam, 2024)
Improving the quality of life in urban areas requires efficient and sustainable infrastructure, especially in the provision of Public Street Lighting (PJU). Cilangkara Village, Bekasi Regency, faces challenges in providing adequate lighting, encouraging the Independent Work Program to implement solar cell and photocell based PJU installations. This technology offers an innovative and sustainable solution, utilizing solar energy through solar cells and automatic photocell regulators. The project implementation method includes community education with outreach on PJU care and maintenance. Science and technology substitution involves solar cell-based PJU technology as an efficient solution with the advantages of energy efficiency, reduced carbon emissions and energy independence. The activity will take place in February 2024, with a focus on installation in Cilangkara Village. The results of the activity include community understanding of the benefits and maintenance of PJUs, as well as the implementation of solar cell-based technology. The conclusion states that this project can provide a positive and sustainable impact, empowering communities and creating efficient infrastructure.